Integration Properties of Disaggregated Solar, Geothermal and Biomass Energy Consumption in the U.S. - Apergis, Nicholas; Tsoumas, C. (Elsevier Science Ltd., 2011)
This paper investigates the integration properties of disaggregated solar, geothermal and biomass energy consumption in the U.S. The analysis is performed for the 1989–2009 period and covers all sectors which use these types of energy, i.e., transportation, residence, industrial, electric power and commercial. The results suggest that there are differences in the order of integration depending on both the type of energy and the sector involved. Moreover, the inclusion of structural breaks traced from the regulatory changes for these energy types seem to affect the order of integration for each series.